Novel approach to monitoring of the soil biological quality - Hofman, Jakub; Bezchlebová, Jitka; Dusek, Ladislav; Dolezal, Ludvík; Holoubek, Ivan; Andel, Petr; Ansorgová, Alena; Malý, Stanislav (Environment international, 2003)
In this study, a new approach to interpretation of results of the simple microbial biomass and respiration measurements in the soil microbiology is proposed. The principle is based on eight basal and derived microbial parameters, which are standardized and then plotted into sunray plots. The output is visual presentation of one plot for each soil, which makes possible the relative comparison and evaluation of soils in the monitored set. Problems of soil microbiology, such as the lack of benchmarking and reference values, can be avoided by using the proposed method. We found that eight parameters provide enough information for evaluation of the status of the soil microorganisms and, thus, for evaluation of the soil biological quality. The usage of rare parameters (potential respiration PR, ratio of potential and basal respiration PR/BR, biomass-specific potential respiration PR/C(bio), available organic carbon C(ext), and biomass-specific available organic carbon C(ext)/C(bio)) can be recommended, besides classical and well-known parameters (microbial biomass C(bio), basal respiration BR, metabolic coefficient qCO(2)). The combination of basal parameters and derived coefficients can also extend our knowledge about the condition of the soil microorganisms. In monitoring the case studies presented, we observed that soils evaluated to possess good biological quality displayed generally higher values of organic carbon, total nitrogen, clay, and cation exchange capacity. The soils of good biological quality can display higher levels of contaminants. This is probably related with the higher content of organic carbon and clay in these soils.
Keywords: silikáty hliníku; jíl; biologické markery; Biomarkers; Biomass; Soil Pollutants; monitorování životního prostředí; látky znečišťující půdu; referenční hodnoty; půdní mikrobiologie; Oxygen; Reference Values; Aluminum Silicates; Environmental Monitoring; Soil Microbiology; Clay; Carbon; uhlík; biomasa; kyslík